Different from the Beginning: WM Maturity of Female and Male Extremely Preterm Neonates—A Quantitative MRI Study - Schmidbauer, V.U.; Yildirim, M.S.; Dovjak, G.O.; Goeral, K.; Buchmayer, J.; Weber, M.; Diogo, M.C.; Giordano, V.; Mayr-Geisl, G.; Prayer, F.; Stuempflen, M.; Lindenlaub, F.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Former preterm born males are at higher risk for neurodevelopmental disabilities compared with female infants born at the same gestational age. This retrospective study investigated sex-related differences in the maturity of early myelinating brain regions in infants born <28 weeks’ gestational age using diffusion tensor– and relaxometry-based MR imaging.MATERIALS AND METHODS: Quantitative MR imaging sequence acquisitions were analyzed in a sample of 35 extremely preterm neonates imaged at term-equivalent ages. Quantitative MR imaging metrics (fractional anisotropy; ADC [10−3mm2/s]; and T1-/T2-relaxation times [ms]) of the medulla oblongata, pontine tegmentum, midbrain, and the right/left posterior limbs of the internal capsule were determined on diffusion tensor– and multidynamic, multiecho sequence–based imaging data. ANCOVA and a paired t test were used to compare female and male infants and to detect hemispheric developmental asymmetries.RESULTS: Seventeen female (mean gestational age at birth: 26 + 0 [SD, 1 + 4] weeks+days) and 18 male (mean gestational age at birth: 26 + 1 [SD, 1 + 3] weeks+days) infants were enrolled in this study. Significant differences were observed in the T2-relaxation time (P = .014) of the pontine tegmentum, T1-relaxation time (P = .011)/T2-relaxation time (P = .024) of the midbrain, and T1-relaxation time (P = .032) of the left posterior limb of the internal capsule. In both sexes, fractional anisotropy (P [♀] < .001/P [♂] < .001) and ADC (P [♀] = .017/P [♂] = .028) differed significantly between the right and left posterior limbs of the internal capsule.CONCLUSIONS: The combined use of various quantitative MR imaging metrics detects sex-related and interhemispheric differences of WM maturity. The brainstem and the left posterior limb of the internal capsule of male preterm neonates are more immature compared with those of female infants at term-equivalent ages. Sex differences in WM maturation need further attention for the personalization of neonatal brain imaging.FAfractional anisotropyGAgestational ageICCintraclass correlation coefficientMDMEmultidynamic multiechoPLICposterior limb of the internal capsulePMApostmenstrual ageT1RT1-relaxation timeT2RT2-relaxation time